Deep Penetration of Shear Deformation in Ferritic Stainless Steel via Differential Speed Rolling Considering Contact Condition - Siti Fatimah; Warda Bahanan; Jee-Hyun Kang; I Putu Widiantara; Young Gun Ko (Applied Sciences)
In order to effectively process crystal-structured materials like metal, knowledge of the working slip system during plastic deformation is necessary. Rolling is a widely utilized industrial processing method, and understanding its inherent characteristics can optimize the process and help achieve the desired microstructure and texture. One key aspect worth investigating is how shear deformation penetrates through the material thickness, particularly in relation to contact conditions. Analyzing slip system activity provides valuable insights into the deep penetration of shear deformation. This is achieved by examining orientation gradients derived from inverse pole figure maps obtained through electron backscatter diffraction. The rotation axis is extracted and compared with that obtained from calculation using simple first-order self-consistent formulation. The analysis was carried out on grains with <semantics><mfenced open="{" close="}" separators="|">001</mfenced><1<mover accent="true">1¯</mover>0></semantics>, <semantics><mfenced open="{" close="}" separators="|">001</mfenced><<mover accent="true">1¯</mover><mover accent="true">1¯</mover>0></semantics>, <semantics><mfenced open="{" close="}" separators="|">111</mfenced><1<mover accent="true">1¯</mover>0></semantics>, <semantics><mfenced open="{" close="}" separators="|">111</mfenced><1<mover accent="true">2¯</mover>1></semantics>, <semantics><mfenced open="{" close="}" separators="|">111</mfenced><0<mover accent="true">1¯</mover>1></semantics>, and <semantics><mfenced open="{" close="}" separators="|">111</mfenced><<mover accent="true">1¯</mover><mover accent="true">1¯</mover>2></semantics> to see the activity of slip systems of <semantics><mfenced open="{" close="}" separators="|">112</mfenced><111></semantics> when plane strain or plane + shear mode is in operation. The rotation axis from the experiment is in agreement with that from the calculation, which confirmed the activity of the well-known <semantics><mfenced open="{" close="}" separators="|">112</mfenced><111></semantics> slip systems. It was found that <semantics><mfenced open="{" close="}" separators="|">112</mfenced><111></semantics> was active in solo in grain with {111}//ND orientation along the γ-fiber during the early stage of differential speed rolling (DSR). Furthermore, it was revealed that the <semantics><mfenced open="{" close="}" separators="|">112</mfenced><111></semantics> slip system was found active when shear deformation mode was in operation at the center of the sheet, which can only be found in the case of a sample with no lubrication. Conclusion: The current study shows that deep penetration was achieved under contact conditions where no lubrication was used during DSR by revealing the activity of the <semantics><mfenced open="{" close="}" separators="|">112</mfenced><111></semantics> slip system under the shear mode of deformation.